The Active Microbiota of the Eggs and the Nauplii of the Pacific Blue Shrimp Litopenaeus stylirostris Partially Shaped by a Potential Vertical Transmission - Giraud, Carolane; Callac, Nolwenn; Boulo, Viviane; Lam, Jean-Sébastien; Pham, Dominique; Selmaoui-Folcher, Nazha; Wabete, Nelly (Frontiers in Microbiology, 2022)
The many ecological niches present in an organism harbor distinct microorganisms called microbiota. Different factors can influence the establishment of these commensal microbial communities. In a previous article, we have hypothesized that some bacterial lineages associated with the early larval stages of the Pacific blue shrimp Litopenaeus stylirostris could be acquired from the breeders via a potential vertical transmission. The present study was conducted in order to investigate this hypothesis. Using HiSeq sequencing of the V4 region of 16S rRNA gene, we analyzed the active microbiota associated with the eggs and the nauplii of L. stylirsotris as well as with the reproductive organs of their breeders. Microbial communities associated with the rearing water were also considered to discriminate environmental factors. Using these analyses, we highlight a set of core bacterial families present in all samples and composed of members of Colwelliaceae, Alteromonadaceae, Pseudoalteromonadaceae, Saccharospirillaceae, Oceanospirillaceae, Vibrionaceae, Burkholderiaceae, Rhodobacteraceae, Flavobacteraceae and Corynebacteriaceae; showing the importance of the environment in the establishment of the larval microbiota. We also present specific bacteria affiliated to the Arcobacteraceae, Rhodobacteraceae, Comamonadaceae and Colwelliaceae families which were only found in the breeders and their offspring strengthening the hypothesis of a potential vertical transmission shaping the active microbiota of the eggs and the nauplii of L. stylirostris.